Organic Acid Changes in the Epidermis of Vicia faba and Their Implication in Stomatal Movement - Pallas, J. E. (1973)
Considerable evidence indicates that the increase in guard cell turgor resulting in stomatal opening is brought about by active K(+) uptake into guard cells. Only a small increase in inorganic anions appears to accompany the increase in K(+). A plausible explanation is that organic acids are produced within guard cells and act as counterions, whereas the H(+) produced are exchanged for K(+). This hypothesis was tested by using different levels of ambient CO(2) in light to control stomatal aperture and at the same time measure changes in organic acid production in the epidermis of Vicia faba. Epidermal strips were used, quickly frozen in liquid nitrogen, and later extracted. A positive correlation was found between stomatal resistance (r(s), indirect measure of stomatal aperture) and CO(2) level. With decreases in r(s), total titratable acidity increased. The organic acids, glyceric, malic, and citric, in the epidermis, as measured by gas chromatography of trimethylsilyl derivatives, increased. Changes in glucose or sucrose were not found. These analyses provided evidence that organic acid production in the epidermis is associated with stomatal opening.